2014
DOI: 10.1002/adsc.201400057
|View full text |Cite
|
Sign up to set email alerts
|

Practical Methods for the Synthesis of Trifluoromethylated Alkynes: Oxidative Trifluoromethylation of Copper Acetylides and Alkynes

Abstract: Two practical and complementary methods are reported for the synthesis of trifluoromethylated alkynes. The first one, a mix-and-stir process, is based on the oxidative trifluoromethylation of readily available and bench-stable copper acetylides while the second one, which displays a broad substrate scope and has several advantages over existing procedures, is based on the oxidative copper-catalyzed direct trifluoromethylation of terminal alkynes. Both reactions provide user-friendly processes for the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 85 publications
1
34
0
Order By: Relevance
“…The Ruppert-Prakash reagent TMSCF3 20 was chosen for this reaction and its optimization, where the high volatility of the trifluoromethylated alkynes 21 formed had to be taken into consideration, revealed that this transformation was best performed using TMEDA as the ligand in a mixture of petroleum ether and DMF. 39 Representative trifluoromethylated alkynes 21 that could be prepared using this transformation which, in comparison with previously reported procedures, does not require heating, nor a source of fluoride to activate the Ruppert-Prakash reagent 20 or slow addition of one reagent, are shown in Figure 8. Besides providing a practical entry to trifluoromethylated alkynes, this oxidative alkynylation of the Ruppert-Prakash reagent demonstrated the possibility of using copper acetylides for the alkynylation of carbon nucleophiles, even poor ones.…”
Section: First Studies Of the Oxidative Alkynylation Of Carbon Nucleomentioning
confidence: 92%
“…The Ruppert-Prakash reagent TMSCF3 20 was chosen for this reaction and its optimization, where the high volatility of the trifluoromethylated alkynes 21 formed had to be taken into consideration, revealed that this transformation was best performed using TMEDA as the ligand in a mixture of petroleum ether and DMF. 39 Representative trifluoromethylated alkynes 21 that could be prepared using this transformation which, in comparison with previously reported procedures, does not require heating, nor a source of fluoride to activate the Ruppert-Prakash reagent 20 or slow addition of one reagent, are shown in Figure 8. Besides providing a practical entry to trifluoromethylated alkynes, this oxidative alkynylation of the Ruppert-Prakash reagent demonstrated the possibility of using copper acetylides for the alkynylation of carbon nucleophiles, even poor ones.…”
Section: First Studies Of the Oxidative Alkynylation Of Carbon Nucleomentioning
confidence: 92%
“…(Trifluoromethyl)alkynes 1 used for type II hydroarylation were prepared from the corresponding terminal alkynes using the modified Evano−Blanchard procedure (Scheme ) ,. New (trifluoromethyl)alkynes 1 d and 1 f were obtained in 68% and 97% yields, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this microreview is to put the different classes of [4+2] cycloadditions of nitrogen‐substituted alkynes into perspective, starting with the electron‐rich ynamine dienophiles that spurred much interest in the 1970s–1990s and continuing with the more stable ynamide dienophiles. In line with our interest in hetero‐Diels–Alder cycloadditions and alkyne chemistry, we recently investigated inverse‐electron‐demand [4+2] cycloadditions of ynamides, and that is the focus of the last part of this microreview [Scheme , Equation (4)] …”
Section: Introductionmentioning
confidence: 99%